Individual Well-Being in a Dynamic Perspective - Conchita D'Ambrosio; Joachim R. Frick (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper explores the determinants of individual well-being as measured by self-reported levels of satisfaction with income. Making full use of the panel data nature of the German Socio-Economic Panel, we provide empirical evidence for well-being depending on absolute and on relative levels of income in a dynamic framework. This finding holds after controlling for other influential factors in a multivariate setting. The main novelty of the paper is the consideration of dynamic aspects: individual's own history as well as the relative income performance with respect to the others living in the society under analysis do play a major role in the assessment of well-being.
Keywords: D63; I31; D31; 330; Interdependent Preferences; Inequality Aversion; Status; Subjective Well-Being; SOEP